2010
DOI: 10.1523/jneurosci.3971-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

eIF2α Phosphorylation-Dependent Translation in CA1 Pyramidal Cells Impairs Hippocampal Memory Consolidation without Affecting General Translation

Abstract: Protein synthesis inhibitor antibiotics are widely used to produce amnesia, and have been recognized to inhibit general or global mRNA translation in the basic translational machinery. For instance, anisomycin interferes with protein synthesis by inhibiting peptidyl transferase or the 80S ribosomal function. Therefore, de novo general or global protein synthesis has been thought to be necessary for long-term memory formation. However, it is unclear which mode of translation-gene-specific translation or general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
101
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 53 publications
8
101
0
Order By: Relevance
“…Because even total blockade of eIF4E-eIF4G interactions would not be expected to block all protein synthesis, this level of protein synthesis reduction was not surprising (5,17,18). However, our results are interesting in the context of previous studies because we found significant memory impairments at levels of protein synthesis blockade below those (either presumed or measured) in previous studies using other protein synthesis inhibitors (12,13,19). Furthermore, these findings combined with a recent report showing that consolidation was more effectively and persistently blocked by anisomycin than was reconsolidation (20) are consistent with our findings of increased eIF4F formation following memory acquisition but not reactivation (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Because even total blockade of eIF4E-eIF4G interactions would not be expected to block all protein synthesis, this level of protein synthesis reduction was not surprising (5,17,18). However, our results are interesting in the context of previous studies because we found significant memory impairments at levels of protein synthesis blockade below those (either presumed or measured) in previous studies using other protein synthesis inhibitors (12,13,19). Furthermore, these findings combined with a recent report showing that consolidation was more effectively and persistently blocked by anisomycin than was reconsolidation (20) are consistent with our findings of increased eIF4F formation following memory acquisition but not reactivation (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Recent evidence supports the idea that eIF2␣ phosphorylation regulates L-LTP and LTM storage through translational control of specific mRNAs, such as ATF4 mRNA. For instance, although general translation is not altered in CA1 neurons, ATF4 protein is increased in the CA1 region from mice in which eIF2␣ is phosphorylated (27). Consistent with these data, Sal003, which increases eIF2␣ phosphorylation, failed to suppress L-LTP in slices from ATF4 knock-out mice compared with WT mice (17).…”
Section: Eif2␣ Phosphorylation: a Master Switch Of Learning And Memorysupporting
confidence: 60%
“…Conversely, hippocampal infusion with a small molecule inhibitor (Sal003), which prevents eIF2␣ dephosphorylation, blocks both L-LTP and LTM formation (17). Jiang et al (27) recently ruled out the possibility that the effects of eIF2␣ phosphorylation on LTM and LTP occur during development. Using a new pharmacogenetic mouse model in which eIF2␣ phosphorylation is selectively increased in CA1 hippocampal neurons (from adult animals) in a time-dependent and inducible manner, they demonstrated that both L-LTP and LTM were impaired (27).…”
Section: Eif2␣ Phosphorylation: a Master Switch Of Learning And Memorymentioning
confidence: 99%
“…Indeed, eIF2␣-KI mice expressed significantly lower ATF4 mRNA levels in the hippocampus compared with WT littermates (eIF2␣-KI, n ϭ 11; eIF2␣-WT, n ϭ 9; t (18) ϭ 2.4, p ϭ 0.03; Fig. 2D), surprisingly demonstrating that a prolonged reduction in phosphorylation levels of eIF2␣ has a bidirectional effect specifically on the transcription of ATF4 (Jiang et al, 2010;Trinh et al, 2012).…”
Section: Resultsmentioning
confidence: 91%